Review and phylogeny of Cyrtomenus Amyot & Serville (Hemiptera: Cydnidae: Cydninae) based on morphological characters - Avendaño, José Mauricio; Correia, Maíra Andrade; Grazia, Jocelia; Schwertner, Cristiano Feldens (Zootaxa, 2024)
Cyrtomenus includes seven species arranged in two subgenera and belongs to the most diverse subfamily of burrower bugs, Cydninae. The species present polyphagous habits, and at least two species are considered crop pests. We conduct a phylogenetic analysis based on morphological characters and two weighting schemes to test its monophyly and the validation of the included subgenera, providing for the first time a phylogenetic hypothesis for the genus. Based on the results, a taxonomic review is presented, including redescriptions of the species, identification key, and distribution maps. Monophyly of Cyrtomenus is supported under implied weighting methods (IW), in both analyses, a clade including species of Prolobodes Amyot & Serville is recognized. The species of these two genera share the posterior tibia strongly flattened, a unique feature among Neotropical Cydninae. The subgeneric classification within Cyrtomenus is not corroborated.